(3QSGdI aj eGgjI GdYTbs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3Ef PGJg jHbi ehLhOkG ehUhakG HGdNjQjI hHcd GdNjQjI s
(3BNQgG (B:s
(3dGf eG jQGe GdJTHjg ef Gdedc GdCYXe dGjDJi Ydi ZGjJg heG jQGe ef GdJTHg ef Gdedhc GdaGfjI bO jDJi Ydi eHdZI hEPG HdZfG HfG GdeHdZ adfNJe GdQSGdI ai eGgjI GdYTb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfi YTQs
(3GdfSNI HgG MhGTs
(3jdjg cJH HGdaGQSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdadSaI hGdefWbs